RELEVANSI TEORI BELAJAR KLASIK DALAM ERA MERDEKA BELAJAR: ANALISIS LITERATUR TERINTEGRASI - Lutfi Alfushilath; Muslim Affandi; MHD Subhan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This article aims to analyze the relevance of classical learning theories in the context of the implementation of the Merdeka Belajar policy in Indonesia through an integrated literature review approach. The classical learning theories examined include behaviorism, early cognitivism, and constructivism as foundational frameworks in the development of educational psychology. Key figures such as B.F. Skinner, Ivan Pavlov, Jean Piaget, and Lev Vygotsky are used as primary references to understand the characteristics of each theoretical perspective. The research method employed is a literature review that integrates various relevant national and international scholarly sources within a specific time frame. The findings indicate that classical learning theories remain relevant in modern educational practices, particularly in aspects of behavior formation, reinforcement, and students’ cognitive structures. However, their application needs to be aligned with the principles of Merdeka Belajar, which emphasize student-centered learning, flexibility, creativity, and the holistic development of individual potential. The integration of classical theories with contemporary learning approaches is essential to create adaptive and contextual learning processes. Therefore, classical learning theories are not entirely obsolete but are reconstructed to align with the dynamics of 21st-century education.